China as a Subject of International Education: Experience of Development - Chengzhang Zou; Weizhen Gao (International Society of Philosophy and Cosmology, 2019)
The phenomenon of internationalization of the space of modern higher education is carried out as basic of the research. Its specific features are distinguished at the contemporary stage of social development. The idea of international education is grounded as a way of formation of cosmopolitanism. The authors examine the positive experience of China in the internationalization of the country's higher education system through the introduction of technical and pedagogical innovations, distance education, the development of language competences and consistent social and educational policies.